PENGARUH KERJA SAMA ORANG TUA DAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI –BP KELAS XI TKJ DI SMK N 1 PUCUK RANTAU KAB. KUANTAN SINGINGI - Sismawati Sismawati; Zulhaini Zulhaini; A Mualif (Universitas Islam Kuantan Singingi, 2023)
The importance of activities in the learning process is a series of activities that include student activity in participating in learning, both thinking, reading and all activities that can support learning outcomes. Based on the observations that the researchers made at the beginning of this study, there were several symptoms, namely (1) students were often late to school, (2) students were less interested in the methods taught by the teacher.This study aims to determine the effect of parent and teacher cooperation in increasing students' learning motivation.The research method used in this study is a quantitative method that is simple linear regression that connects 2 variables, the sample in this study amounted to 59 people, including: 29 students and students of class XI TKJ, and 29 parents and guardians of students from class XI TKJ. XI TKJ, 1 PAI-BP teacher. Based on data analysis, the coefficient of determination (R square) is 0.070 squared (0.265 X 0.265 = 0.7022). The magnitude (R square) is 0.070 = 7%, this means that there is an effect of parent and teacher cooperation on student learning motivation at SMK N 1 Pucuk Rantau, Kuantan Singingi Regency.